Natural Gas Dehydration by Absorption Process: A comparative simulation study towards high effective natural gas dehydration using TEG technology - Muhammad Aimen Bin Isa, Muhammad Aimen (UNIVERSITI TEKNOLOGI PETRONAS, 2011)
Natural gas dehydration by absorption using triethylene glycol (TEG) is one of the most effective techniques with high efficiency. There are many processes using this approach but any of them is able to combine the high performance and the economic energy consumption. In this study water hydrocarbon phase behavior was determined for different gas dehydration unit. The effects of the operating conditions of the gas dehydration unit in determining the outlet gas dew point and water content remaining in dry gas were studied by means of simulation run using ASPEN HYSYS software. DRIZO process showed the most significant change of water dew point curve followed by conventional stripping gas dehydration process and then the typical gas dehydration process. At the other hand, study was done on improving the absorption capacity of TEG as the water absorbent by adding additives to the absorbent. Lastly, comparisons between theoretical and simulation results are justified to determine whether it shows a good validation of the results to meet the requirements of current industry practices.